2018
DOI: 10.1002/joc.5463
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tropical cyclone activity in north Indian Ocean during satellite era (1981–2014)

Abstract: Recent findings have raised the debate on increase in tropical cyclone activity (TCA) in major tropical ocean basins like North Atlantic and western North Pacific. To address the similar evidence in North Indian Ocean (NIO) basins, an attempt has been made in the present study to investigate TCA in NIO basins in the context of warmer climate during the satellite era (1981–2014). The most suitable cyclone energy metric called accumulated cyclone energy (ACE) is estimated for this purpose. A statistical change‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…Using global coupled models, Jiang et al (2018) suggested that the predictability of TC genesis is closely linked to the model predictability of several large-scale dynamic and thermodynamic fields. Change-point detection analysis of accumulated cyclonic energy (ACE) carried out by Balaji et al (2018) revealed that there is a shift in ACE in recent decades. Specifically, ACE started increasing from 1997, and the observed twofold increase in ACE was due to the increase in the number and duration of very severe cyclonic storms in the satellite era (1981−2014).…”
Section: Introductionmentioning
confidence: 99%
“…Using global coupled models, Jiang et al (2018) suggested that the predictability of TC genesis is closely linked to the model predictability of several large-scale dynamic and thermodynamic fields. Change-point detection analysis of accumulated cyclonic energy (ACE) carried out by Balaji et al (2018) revealed that there is a shift in ACE in recent decades. Specifically, ACE started increasing from 1997, and the observed twofold increase in ACE was due to the increase in the number and duration of very severe cyclonic storms in the satellite era (1981−2014).…”
Section: Introductionmentioning
confidence: 99%
“…Figure a illustrates the cyclonic activity over BoB at its Cyclonic Stages (CS), and severe cyclone and above stages. There are several studies dealing with the cyclonic activity over BoB (Balaguru et al, ; Balaji et al, ) and they point towards increasing cyclonic activity over the bay. In recent years, most of the cyclones were identified to reach the intensity of severe cyclones and above categories.…”
Section: Resultsmentioning
confidence: 99%
“…The TC activity variation is related to SST, UOHC, TCWV, RH, LTT, and VWS. Balaji [36] [25,28,47]. On a monthly basis, TC activity was strong in November (13 TCs), October (12 TCs), May (8 TCs), and December (7 TCs) ( Figure 1b).…”
Section: Tc Activity In the Bay Of Bengalmentioning
confidence: 98%